Growth regulator and maize response to the increase in plant density - Leolato L.S.* (2017)
The objective of this work was to evaluate the effect of application of the growth regulator Trinexapac-ethyl on maize response to the increase in plant density at two sowing dates. A field experiment was carried out in the municipality of Lages, state of Santa Catarina, Brazil, during the 2014/2015 and 2015/2016 growing seasons. Two sowing dates (10/15 - preferential, and 12/5 - late), four plant densities (5, 7, 9, and 11 plants m-2), with and without Trinexapac-ethyl application, were tested. The growth regulator was sprayed at a rate of 150 g a.i. ha-1, when hybrid P30F53YH was at the V5 and V10 growth stages. The spraying of Trinexapac-ethyl decreased the stem length above the ear insertion node at both growing seasons. Grain yield ranged from 11,422 to 14,805 kg ha-1, and increased in a quadratic way with the increment in plant density. The highest yields were reached when maize was sown in October. The spraying of Trinexapac-ethyl did not affect grain yield, but decreased the 1,000 kernels mass at both sowing dates. The use of Trinexapac-ethyl does not enhance grain yield of maize hybrid P30F53YH at crowded stands in response to the densification, regardless of sowing time.